Metamorphosis (Science Series for the 21st Century Learners) 7 - Matira, Myrna D.; Chico, Alegria M.; Fabian, Jeannette C.; Hingcoy, Delia F. (Sampaloc, Manila. St. Augustine Publications, Inc., 2015)
"Your metamorphosis in this grade level begins by learning to distinguish mixtures from substances through semi-guided investigations. Realize the importance of air testing when conducting investigations for the First Quarter. After studying how organ systems work together in plants and animals in the lower grade levels, enjoy using a microscope when observing very small organisms and structures".
English text.
Keywords: Mathematics -- Study and Teaching; Science -- Study and Teaching